Transformer Condition Assessment Using Artificial Intelligence - Ghunem, Refat Atef (2010)
A Master of Science Thesis in Electrical Engineering Submitted by Refat Atef Ghunem Entitled, "Transformer Condition Assessment Using Artificial Intelligence," May 2010. Available are both Soft and Hard Copies of the Thesis.